2017
DOI: 10.1186/s13071-017-2276-4
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid induces a transient shift in signaling that enhances NF-κB-mediated parasite killing in the midgut of Anopheles stephensi without reducing lifespan or fecundity

Abstract: BackgroundAbscisic acid (ABA) is naturally present in mammalian blood and circulating levels can be increased by oral supplementation. We showed previously that oral ABA supplementation in a mouse model of Plasmodium yoelii 17XNL infection reduced parasitemia and gametocytemia, spleen and liver pathology, and parasite transmission to the mosquito Anopheles stephensi fed on these mice. Treatment of cultured Plasmodium falciparum with ABA at levels detected in our model had no effects on asexual growth or gameto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 69 publications
2
14
1
Order By: Relevance
“…In contrast to our prediction, median survival in adult females derived from larvae treated with ABA was reduced to 28 ± 10.78 days (1 µM ABA; log rank p = 0.028) and to 30 ± 14.22 days (100 µM ABA; two-stage p = 0.025) relative to the untreated control median lifespan of 34 ± 14.2 days (Figure 7). Consistent with previous observations of no effect of ABA in blood on adult female lifespan (Glennon et al, 2017), the addition of 100 nM ABA in the blood meal had no effect on adult lifespan nor did it alter the effects of larval treatment with ABA on adult lifespan ( Supplementary Table S4).…”
Section: Adult Female a Stephensi Derived From Aba-treated Larvae Exsupporting
confidence: 89%
See 4 more Smart Citations
“…In contrast to our prediction, median survival in adult females derived from larvae treated with ABA was reduced to 28 ± 10.78 days (1 µM ABA; log rank p = 0.028) and to 30 ± 14.22 days (100 µM ABA; two-stage p = 0.025) relative to the untreated control median lifespan of 34 ± 14.2 days (Figure 7). Consistent with previous observations of no effect of ABA in blood on adult female lifespan (Glennon et al, 2017), the addition of 100 nM ABA in the blood meal had no effect on adult lifespan nor did it alter the effects of larval treatment with ABA on adult lifespan ( Supplementary Table S4).…”
Section: Adult Female a Stephensi Derived From Aba-treated Larvae Exsupporting
confidence: 89%
“…In our previous studies, we observed that ingestion of an ABA-supplemented blood meal by female A. stephensi induced signaling kinases associated with a transient metabolic shift in the midgut, fueling immune-mediated killing of P. falciparum prior to completion of oocyst development (Glennon et al, 2016(Glennon et al, , 2017. Interestingly, ingested ABA did not decrease A. stephensi fecundity in the first gonotrophic cycle in contrast to our predictions based on the effects of ABA in A. elliotti and in S. bullata (Glennon et al, 2017).…”
Section: Introductioncontrasting
confidence: 82%
See 3 more Smart Citations